Teaching dancing with ideokinetic principles - Williams, Drid, 1928-2018 (University of Illinois Press, 2011)
"In examining ideokinesis and its application to the teaching and practice of dancing, Drid Williams introduces readers to the work of Dr. Lulu Sweigard (1895-1974), a pioneer of ideokinetic principles. Drawing on her experiences during private instructional sessions with Sweigard over a two-year span, Williams discusses methods using imagery for improving body posture and alignment for ease of movement. Central to Williams's own teaching methods is the application of Sweigard's principles and general anatomical instruction, including how she used visual imagery to help prevent bodily injuries and increasing body awareness relative to movement. Williams also emphasizes the differences between kinesthetic (internal) and mirror (external) imagery and shares reactions from professional dancers who were taught using ideokinesis. Williams's account of teaching and practicing ideokinesis is supplemented with essays by Sweigard, William James, and Jean-Georges Noverre on dancing, posture, and habits. Teaching Dancing with Ideokinetic Principles offers an important historical perspective and valuable insights from years of teaching experience into how ideokinesis can shape a larger philosophy of the dance"--Provided by publisher.